The Relationship between Family Burden and Social Support in Caregivers of Schizophrenic Patients in Kermanshah City, 2019 - Soroush Maazinezhad; Mohammad-Rafi Bazrafshan; Vahab Karamivand; Mahmoud Rahmati (Shiraz University of Medical Sciences, 2019)
Background: Schizophrenia, as a chronic and debilitating disease, has consequences not only for the patient but also for the family and society. It severely destroys the energy and resources available to the patient's family. The purpose of this study was to investigate the relationship between the burden on caregivers of schizophrenic patients and their perceived social support. Methods: In this cross-sectional study, the statistical population consisted of all Caregivers of schizophrenic patients referred to Farabi Psychiatric Center of Kermanshah in 2019. Out of them, a sample of 125 individuals was selected by the convenience sampling method. Two standard questionnaires, family burden interview schedule, and Social support inventory were used to assess the family burden and social support. Results: The mean age of the participants was 42.69±12.78 years. The results showed the mean score of social support in the individuals as 14.72±5.93. Furthermore, the mean score of the family burden was found at 28.03±11.03. There was a significant statistical reverse correlation between social support and family burden (p<.001, r=-378). The regression model showed that social support could predict family pressure. The collected data were analyzed using descriptive statistics and analytical statistics (chi-squared, Spearman's, and linear regression), where the significance level was set at 0.05. (P<0.05). Conclusion: Caregivers of schizophrenic patients are exposed to high psychological, economic, and social pressures. This can be effective in reducing the quality of patient care. Therefore, increasing the level of social support in these people is essential in reducing the complications of schizophrenia.